Parental support and influencing factors for school-age children's healthy movement behavior: a cross-sectional study - Rachmawati, Praba Diyan; Krisnana, Ilya; Pradanie, Retnayu; Qur'aniati, Nuzul; Arief, Yuni Sufyanti; Biru, Mustika Milenia Dwi Tunjung; Asih , Meirina Nur; Rithpho, Pratuma; Kurnia, Iqlima Dwi (Jurnal Ners, 2024)
Introduction: Optimizing healthy lifestyles in children requires parental support for healthy movement behaviors. This study analyzed factors influencing parental support for school-age children's movement activities. Methods: This study employed an analytic descriptive design with a cross-sectional approach, involving a sample of 355 mothers with school-age children. The independent variables included family, child, and environmental factors, whereas the dependent variable was parental support for healthy movement behaviors, as assessed through a questionnaire. Data analysis was performed using binary logistic regression with backward elimination. Results: The factors that significantly influenced parental support for their children's engagement in light physical activities included the children's own level of participation in such activities (OR=2.52, 95% CI=0.76-6.67). Factors affecting support for moderate to vigorous activities were maternal exercise habits (OR=3.37; 95% CI=1.18-9.65), children's sports habits (OR=5.18; 95% CI=1.64-16.26), and the presence of personal gadgets (OR=0.45, 95% CI=0.23-0.86). Parental support for preventing sedentary behaviors was influenced by parental knowledge (OR=2.33; 95% CI=1.34-4.05), mother's sleep duration (OR=2.46; 95% CI=1.27-4.75), and gadgets (OR=0.55; 95% CI=0.31-0.95). Factors affecting support for adequate sleep included children's light activities (OR=3.42; 95% CI=1.27-9.23) and their ownership of personal gadgets (OR=0.44; 95% CI=0.24-0.79) Conclusions: Parental support is influenced by the knowledge and physical activity habits of both mother and child, as well as gadget use and maternal sleep patterns. Pediatric nurses can enhance this support through health education focused on promoting healthy movement behaviors within families.